Current Ratio dan Debt to Equty Ratio Pengaruhnya Terhadap Harga Saham - Nurjaya, Nurjaya; Artiyanty, Megahati; Alamsyah, Fitri Angraeni (Journal of Business and Economics Research (JBE), 2023)
This study aims to determine the effect of the Current Ratio (CR) and the Debt To Equity Ratio (DER) partially and simultaneously on the stock price at PT. Fajar Surya Wisesa, Tbk. The research method used is quantitative by analyzing and describing the condition of the company using data from financial reports. The object of this research is PT. Fajar Surya Wisesa, Tbk. The research data used is data from the 2012-2021 financial reports. The results showed that Current Ratio (CR) had no significant effect on stock prices at PT. Fajar Surya Wisesa, Tbk obtained a t-count value of 0.27 < t-table of 2.364 with a significance value (sig) of 0.797. The results of the Debt To Equity Ratio (DER) study have a significant effect on the stock price at PT. Fajar Surya Wisesa, Tbk obtained a t-count value of -3.333 < t-table -2.364 with a significance value (sig) of 0.013. The results of research on Current Ratio (CR) and Debt To Equity Ratio (DER) simultaneously have a significant effect on stock prices at PT. Fajar Surya Wisesa, Tbk with an Fcount of 6.496 > Ftable of 4.35 with a significant value (sig) of 0,025.